2015
DOI: 10.1523/jneurosci.0887-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

mTORC2/Rictor Signaling Disrupts Dopamine-Dependent Behaviors via Defects in Striatal Dopamine Neurotransmission

Abstract: Disrupted neuronal protein kinase B (Akt) signaling has been associated with dopamine (DA)-related neuropsychiatric disorders, including schizophrenia, a devastating mental illness. We hypothesize that proper DA neurotransmission is therefore dependent upon intact neuronal Akt function. Akt is activated by phosphorylation of two key residues: Thr308 and Ser473. Blunted Akt phosphorylation at Ser473 (pAkt-473) has been observed in lymphocytes and postmortem brains of schizophrenia patients, and psychosis-prone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 82 publications
2
54
0
Order By: Relevance
“…In line with these observations, haloperidol has been associated with rpS6 phosphorylation at Ser235/236, specifically at the level of DRD2 MSN cells in the indirect striatopallidal pathway [40]. Recently, Dadalko et al [16] demonstrated the involvement of mTORC2 signaling in the regulation of the striatal dopamine (DA) tone and D2R signaling. Additionally, they showed that the changes in striatal DA neurotransmission and associated behaviors are caused by elevated DRD2 expression.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In line with these observations, haloperidol has been associated with rpS6 phosphorylation at Ser235/236, specifically at the level of DRD2 MSN cells in the indirect striatopallidal pathway [40]. Recently, Dadalko et al [16] demonstrated the involvement of mTORC2 signaling in the regulation of the striatal dopamine (DA) tone and D2R signaling. Additionally, they showed that the changes in striatal DA neurotransmission and associated behaviors are caused by elevated DRD2 expression.…”
Section: Discussionmentioning
confidence: 73%
“…Recently, various authors have implicated the mTOR signaling pathway in the modulation exerted by AP drugs such as thioridazine [12,13], olanzapine [14], haloperidol [15,16] and risperidone [17], among others. In parallel, several studies provide evidence for the involvement of disrupted mTOR signaling in the neuropathology of schizophrenia [18].…”
Section: Introductionmentioning
confidence: 99%
“…Increased mTOR signaling in the dorsal and ventral striatum could contribute to the adaptations in locomotor behavior [99] and reward pathway sensitivity [100102] known to occur following habitual physical activity. It is somewhat surprising that exercise did not increase p-mTOR in the DMS, especially considering that exercise elicits other adaptations in this region including changes in mRNA levels of dopamine and opioid receptors [72, 103], 5-HT2C receptors [104], and increases in ΔFosB [70].…”
Section: Discussionmentioning
confidence: 99%
“…However, the decrease in striatal ser31 TH phosphorylation in the DAT +/− and DAT −/− indicates that some DA-mediated D 2 regulation is still present, as antagonists also increase ser31 in striatum. 18 The DA D 2 receptor is coupled to ERK function, 10 and given the reported decrease in autoreceptor function in DAT +/− and DAT −/− genotypes, the decrease in ser31 TH phosphorylation, a target of ERK under depolarizing conditions, 7 would be expected. This differential response in ser31 and ser40 phosphorylation in both nucleus accumbens and striatum indicates that, under the conditions of DA neurotransmission imposed by the loss of DAT, autoreceptor-mediated control of only ser40 may be abrogated, and the segregation of phosphorylation differences in response to physiological stimuli at these two sites has been observed in other paradigms studying TH regulation in vivo .…”
Section: Discussionmentioning
confidence: 99%